Searching for an alternative to manage powdery scab, caused by Spongospora subterranean, in potato (2018)
One of the main problems in potato production is powdery scab, caused by the protozoan Spongospora subterranea. Currently, there are no effective control strategies for this pathogen, which causes root damage and, therefore, reduces tuber quality. In order to develop a biocontrol alternative for powdery scab, we assessed the effect of eight potential microbial agents belonging to the genera Trichoderma spp., Pseudomonas sp., Bacillus sp. and Streptomyces spp. in the reduction of the disease. Additionally, we evaluated biocarbon, chitin and chitosan, which are organic additives with a biocontrol potential in other pathosystems. Initially, a trial was established to obtain the development of galls in two different locations (Mosquera and Subachoque, Cundinamarca) with two concentrations of protozoan inoculum. Eight weeks after sowing, the disease severity was determined counting the number of galls per plant. Because of the consistent development of the disease, the assays were established in the municipality of Subachoque in potted plants with naturally infested soil (1×103 sporosori/g of soil). All microbial biocontrol agents showed a reduction in gall development (P>0.05). Streptomyces misionensis Ac006 caused the largest reduction in severity (51.41%). Among the organic additives, 0.5% chitosan had the greatest (62.58%) effect on disease reduction, a significant (P≤0.05) effect. Our results suggest possible alternatives for the sustainable management of powdery scab in potato.